EFEKTIVITAS COGNITIVE BEHAVIOUR MODIFICATION (CBM) TERHADAP PERILAKU MALU PADA SISWA MAKN SURAKARTA - Lestari, Sumi (Jurnal Interaktif, 2010)
This research study is about lose face behavior which is one of feel that must be left on individual to adapting as well, make a good communication andÂ  actualization of potential as well. This research use lose face behavior of Zimbardo scale, sheet of permission subject, sheet of contract job, daily duty, and training evaluation. Subject of this research compossed of two groups, experiment group and control group. Characteristics of this subject are teenager of 15-18 years old, grade 2-3, moslem, have average until very high score data collectingÂ  by alloting scale at each subject research on MAKN Surakarta student. Result of hypothesis test obtained by using aid SPSS program for Windows. 10.0.Result of the research show: cognitive behavior modification training which passed to MAKN Surakarta students are significant or cognitive behavior modification training effective to degrade behavior lose face of MAKN Surakarta student, as according to difference assess average on experiment group and control group after training (post test1) and two weeks after training (post test2); lose face behavior value on experiment group lower than control group. At value of post-test1 and post-test2; control group show the increase value of lose face behavior because of not given cognitive behavior modification training.Key words: Effectiveness, CBM, Behavior lose face, student.